The Little Data Book on Private Sector Development 2014 - WorldBank, WorldBank (World Bank, 2015)
One of a series of pocket-sized books that provide a quick reference to development data on different topics, 'The Little Data Book on Private Sector Development 2014' provides data for more than 20 key indicators on the business environment and private sector development in a single page for each of the World Bank member countries and other economies with populations of more than 30,000. The 200 country pages are supplemented by aggregate data tables by regional and income groupings.